Exploration of Nutritional Knowledge Aspects of Pregnant Adolescents in Javanese Ethnicity in Ponorogo Regency, East Java - Retno Inten Rizki P; Rahayu Indriasari; Baharuddin Bahar; Abdul Razak Thaha; Hasanuddin Ishak; Abdul Salam (Journal La Medihealtico, 2020)
Maternal health problems are one of the main indicators of health status, namely maternal mortality. Maternal mortality is still a major public health challenge around the world, including in Indonesia. The purpose of this study was to explore aspects of nutritional knowledge related to healthy food, balanced nutrition, exclusive breastfeeding and care during teenage pregnancy for Javanese ethnicity in Ponorogo, East Java. This type of research is qualitative with a phenomenological approach. This research was conducted in June - July 2020. The main informants in this study were pregnant women aged 10-19 years in the working area of ​​the Balong Community Health Center, Ponorogo Regency. The source of the informants was determined by snowball sampling. The snowball sampling technique is a form of judgment sampling. Data collection is more emphasized through in-depth interviews (in-depth interviews), namely individual dialogue with informants obtained directly from pregnant women. The results of the study of 6 informants who were teenage pregnant women in the Balong PKM work area, Ponorogo Regency, all informants had underweight nutritional status (BMI / age) and Chronic Energy Deficiency (KEK). The knowledge explored in the form of: food for pregnant women, balanced nutrition, exclusive breastfeeding, risk of teenage pregnancy and pregnancy care. Based on the results of the interview, the informant said that foods that are good for pregnant women to consume are fruits, vegetables, milk and vitamins. Regarding balanced nutrition, all informants did not know at all what balanced nutrition for care during pregnancy, the informant said there was no difference in pregnancy care except health checks at health services, treatments such as maintaining cleanliness and regular exercise.